Cardiovascular Disease Prediction Using Gradient Boosting Classifier - Suhendra, Rivansyah; Husdayanti, Noviana; Suryadi, Suryadi; Juliwardi, Ilham; Sanusi, Sanusi; Ridho, Abdurrahman; Ardiansyah, Muhammad; Murhaban, Murhaban; Ikhsan, Ikhsan (Heca Sentra Analitika, 2023)
Cardiovascular Disease (CVD), a prevalent global health concern involving heart and blood vessel disorders, prompts this research's focus on accurate prediction. This study explores the predictive capabilities of the Gradient Boosting Classifier (GBC) in cardiovascular disease across two datasets. Through meticulous data collection, preprocessing, and GBC classification, the study achieves a noteworthy accuracy of 97.63%, underscoring the GBC's effectiveness in accurate CVD detection. The robust performance of the GBC, evidenced by high accuracy, highlights its adaptability to diverse datasets and signifies its potential as a valuable tool for early identification of cardiovascular diseases. These findings provide valuable insights into the application of machine learning methodologies, particularly the GBC, in advancing the accuracy of CVD prediction, with implications for proactive healthcare interventions and improved patient outcomes.